Визначення часу опроміненя поверхні інкубаційного яйця при лазерній обробці - Міленін, Д. М. (Енергетика і автоматика, 2017)
DEFINITION OF TIME EXPOSURE SURFACE hatching eggs in the laser treatment D. Milenin Annotation. The laser surface treatment conditions of the egg shell as it rotates around the major axis of the ellipsoid which it describes. Determine otpimal time spent shell surface under the radiation source. Key words: laser, radiation dose, incubation eggs